HDL and its subpopulation (HDL2 AND HDL3) promote cholesterol transporters expression and attenuate inflammation in 3t3-l1 mature adipocytes induced by tumor necrosis factor-alpha - Suhaila Abd Muid,; Remee Awang Jalil,; Noor Hanisa Harun,; Hapizah Mohd Nawawi,; Froemming, Gabriele Ruth Anisah (Penerbit Universiti Kebangsaan Malaysia, 2022)
Obesity activates inflammation causing dysfunction of adipocytes. Increasing high-density lipoprotein (HDL) levels in obesity may be beneficial in overcoming this effect. However, not much data is available on the effects of HDL and its subpopulations in inflamed adipocytes. The objective of this study was to investigate the effects of total HDL (tHDL) and the comparison between its subpopulations (HDL2 & HDL3) on protein and gene expression of cholesterol transporters, inflammation, and adipokines in TNF-α stimulated 3T3-L1 mature adipocytes. TNFα alone had lower adiponectin and higher protein and gene expression of IL-6 and NF-ĸβ (p65) compared to unstimulated adipocytes and these effects were attenuated by HDLs especially HDL3 (in most of the biomarkers). HDL and its subpopulation had higher cholesterol transporters expression in 3T3-L1 mature adipocytes induced by TNF-α compared to unstimulated cells. Increment of cholesterol transporters expression by HDL leads to reduce secretion of inflammatory markers [IL-6 & NF-kB (p65)] and visfatin and increases adiponectin secretion in the inflamed mature adipocytes. HDL exhibits beyond its reverse cholesterol transporter property by exhibiting anti-inflammatory effects thru the deactivation of NF-ĸβ (p65). This may contribute to reducing the progression of obesity-related complications.